Bilateral chylothorax – complication after cardiac surgical intervention in neonates – case report - Hristina Mandzukovska (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2018)
ABSTRACT Background: Chylothorax is a rare complication after cardiac surgery of congenital heart diseases. In majority of cases treatment is conservative and long-lasting. In rare cases a surgical intervention is necessary. Case report: We present a case of a seven-month infant with congenital heart defect, which was diagnosed in the first days of his life. A cyanogenic heart defect –single ventricle, TGA, pulmonaly stenosis, PDA, was detected. During the cardiac surgery a Glenn procedure was realized. In the postoperative period deterioration of the general condition was observed along with respiratory insufficiency, onset of bilateral pleural effusion, chylothorax that was confirmed with cytological and biochemical examinations. Conservative treatment with low-fat diet was conducted. After one month of hospitalization and treatment at the Department of Intensive Care ( ICU ), there was an improvement in the condition and the infant was referred to another department. Conclusion: Onset of chylothorax following cardiac surgery is a complication, which usually appears during intervention in the aortic arch and single ventricle. The first choice of treatment is conservative one, with enteral intake of milk rich in long-chain free fatty acids and medium-chain triglycerides. If there is no improvement in the condition, a surgical intervention is necessary.
Keywords: chylothorax; congenital heart diseases; cardiac surgery; conservative treatment